DAMPAK SOSIAL EKONOMI PROGRAM PEMBAGIAN BERAS MISKIN DI KECAMATAN RANTEBULAHAN TIMUR KABUPATEN MAMASA - Abd. Asis; Rosdiana Rosdiana (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Al Asyariah Mandar, 2019)
This study aims to determine the socio-economic impact of the poor rice distribution program (Raskin) in the East Rantebulahan Subdistrict, Mamasa Regency. The type of research used is descriptive research. Data obtained through interviews, observations with direct observations at the location of research, documentation, and analyzed qualitatively. The results showed that the distribution of Raskin in Rantebulahan Timur Sub-district did not have an economic impact after the community received raskin. Because after receiving Raskin, the income they earn is only enough to meet food needs, not yet reaching for the fulfillment of clothing and shelter. Another impact of the distribution of Raskin was the socio-cultural impact, where Raskin did not affect the socio-cultural conditions of Raskin recipients.